2023
DOI: 10.3390/agriculture13020343
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Structural Sugar Metabolism in Regulating Tuber Dormancy in White Yam (Dioscorea rotundata)

Abstract: Changes in sugar composition occur continuously in plant tissues at different developmental stages. Tuber dormancy induction, stability, and breaking are very critical developmental transitions in yam crop production. Prolonged tuber dormancy after physiological maturity has constituted a great challenge in yam genetic improvement and productivity. In the present study, biochemical profiling of non-structural sugar in yam tubers during dormancy was performed to determine the role of non-structural sugar in yam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…our result is an agreement with the findings of [94,95] and the report of Wengler; [92]. Also, we earlier reported that biochemical profiling of non-structural sugar from yam tuber dormancy to dormancy break revealed that quantity of nonreducing sugar which include sucrose increased up to 9 and 10 folds in the tubers of TDr110073 and Obiaoturugo respectively and that this increase started from 56-DAPM in tubers of Obiaoturugo and 101-DAPM in tubers of TDr1100873 [44]. This Indicates that sucrose play role in the early cellular activities culminating in dormancy break in the tubers of both genotypes.…”
Section: Energy Metabolismsupporting
confidence: 93%
See 3 more Smart Citations
“…our result is an agreement with the findings of [94,95] and the report of Wengler; [92]. Also, we earlier reported that biochemical profiling of non-structural sugar from yam tuber dormancy to dormancy break revealed that quantity of nonreducing sugar which include sucrose increased up to 9 and 10 folds in the tubers of TDr110073 and Obiaoturugo respectively and that this increase started from 56-DAPM in tubers of Obiaoturugo and 101-DAPM in tubers of TDr1100873 [44]. This Indicates that sucrose play role in the early cellular activities culminating in dormancy break in the tubers of both genotypes.…”
Section: Energy Metabolismsupporting
confidence: 93%
“…while botanical seeds are in desiccation state at maturity necessitating their requirement of imbibition during germination process, yam tubers at maturity are in hydrated state, and do not require imbibition during germination. Instead, as we reported earlier [44], it requires moisture loss to 40% threshold before dormancy breaking process can commence.…”
Section: Identification Of Differentially Accumulated Metabolites Acr...mentioning
confidence: 67%
See 2 more Smart Citations
“…While botanical seeds are in the desiccation state at maturity, necessitating their requirement of imbibition during the germination process, yam tubers at maturity are in the hydrated state, and do not require imbibition during germination. Instead, as we reported earlier [ 44 ], it requires moisture loss to a 40% threshold before the dormancy-breaking process can commence. This might be linked to this sharp deviation of yam tuber germination stages from well-established three curve stages of the germination process in botanical seeds.…”
Section: Resultsmentioning
confidence: 83%